2006
DOI: 10.1139/h06-014
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity during treatment in children with leukemia: a pilot study

Abstract: The purpose of this pilot study was to measure physical activity (PA) levels in children undergoing treatment for acute lymphoblastic leukemia (ALL) and to compare the results with those from age-matched healthy children. We used the MTI Actigraph accelerometer to determine PA (during a 1 week period) in children (n = 7; age = 4-7 y) undergoing maintenance treatment for ALL and in age-matched controls (n = 7). The number of children accumulating at least 60 min of moderate-to-vigorous physical activity (MVPA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 28 publications
5
63
2
2
Order By: Relevance
“…These results are in accordance with those of Aznar et al, who also found a lower physical activity in ALL patients compared to healthy controls [2]. As far as we know, there are no further studies on physical activity measured in ALL patients on treatment.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with those of Aznar et al, who also found a lower physical activity in ALL patients compared to healthy controls [2]. As far as we know, there are no further studies on physical activity measured in ALL patients on treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Children undergoing the early stages of treatment have reduced PA, mainly because of the constraints associated with hospitalization, which include medical apparatus, and side effects from intensive treatment regimes, such as fatigue and nausea, which lead to sedentary bed rest. 37,38 A spectrum of disuse, and overprotective parents and physicians monitoring children in remission, may contribute to patterns of inactivity persisting after treatment is completed. 39 Although five children in the current study had PAQ-C scores lower than published mean scores for children without a cancer diagnosis (mean score 3.2), 22 two children had comparable scores, and six achieved higher scores.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivity (5-7), impaired cardiopulmonary and musculoskeletal function, as well as reduced motor performance levels (8,9) and cognitive abilities (10) have been detected. Current studies also examined a negative impact on psychological well-being, satisfaction, and social functioning (11). Taken together, an impaired quality of life can thus be determined (8,12).…”
mentioning
confidence: 99%